USE OF PLASMA CURRENTS IN SURGERY OF PURULENT AND INFLAMMATORY DISEASES - A. M. Shulutko; E. G. Osmanov; F. N. Nasyrov; A. Yu. Krylov; D. M. Djamalov (Сеченовский вестник, 2010)
Aim of the study. Evaluation of efficacy of plasma currents in treatment of soft tissue wounds.Materials and methods. 682 patients with purulent inflammation of soft tissues were included into the study: in all of them argon and plasma-air currents were used. The results were compared with 440 patients, who received only standard therapeutic regimens.Results. Use of plasma-air currents was associated with diminishing of frequency of necrectomy procedures, intra-operative blood loss and postoperational pain. Plasma current accelerated necrolysis, regeneration and epythelisation of wound defect, as well as reduction of paravasal inflammation in patients with thrombophlebitis.Conclusion. Plasma current use is effective in treatment of inflammatory diseases of soft tissues.